The Use of Free Learning Prototype Curriculum in Blended Learning to Improve the Quality Counseling Technique Practice Lectures for Student Guidance and Counseling Study Program - Gusman Lesmana; Sri Ngayomi Yudha Wastuti; Deliati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Implementation of the independent learning campus policy is to encourage a more independent and flexible quality of learning in higher education. Only a few of the students were able to follow this development. The aims of this study is to analyze implementation of free learning prototype curriculum in blended learning to improve the quality counseling technique practice lectures for student guidance and counseling study program.This study uses a quantitative approach to the type of experiment. The population in this study were students of the Guidance and Counseling study program, who were taking the Counseling Approach course in the even semester of 2021/2022. The instrument used is a questionnaire instrument with a Likert scale model. The results of the reliability test of the lecture quality instrument were 0.922. The research data were analyzed using Pearson Product Moment Correlation. The research findings show that with the correlation obtained from the SPSS output display model summary 26.00 showing the magnitude of the hypothesis test results obtained r-count = 0.329 and r-table = 0.312 so that the results of r-count > r-table (0.329 > 0.312). This shows that there is a positive influence on the strategy of using the independent learning curriculum to improve the quality of lectures in a positive direction.